2010
DOI: 10.3920/bm2010.0019
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of lactobacilli isolated from Kimere, a spontaneously fermented pearl millet dough from Mbeere, Kenya (East Africa)

Abstract: The objective of the study was to isolate potential probiotic lactobacilli from Kimere, a pearl millet dough prepared in the Mbeere community of Kenya, East Africa, by fermentation for 18-24 hours. Kimere samples, collected from 11 different homesteads in Mbeere, showed average pH values of 3.63±0.29. Counts of presumptive lactobacilli were 8.52±0.02 log10 colony forming units per gram, respectively. 48 presumptive Lactobacillus isolates were characterised and identified by biochemical and molecular methods. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In this study we found that some strains of L. fermentum , isolated from Kimere 13, enhanced hBD‐2 secretion by intestinal epithelial cell line CaCo‐2 in time‐, dose‐, and particularly strain‐specific manner. Among 11 tested strains only two, namely L. fermentum strains K2‐Lb6 and K11‐Lb3, significantly induced hBD‐2 secretion.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In this study we found that some strains of L. fermentum , isolated from Kimere 13, enhanced hBD‐2 secretion by intestinal epithelial cell line CaCo‐2 in time‐, dose‐, and particularly strain‐specific manner. Among 11 tested strains only two, namely L. fermentum strains K2‐Lb6 and K11‐Lb3, significantly induced hBD‐2 secretion.…”
Section: Discussionmentioning
confidence: 62%
“…Previously, we isolated and characterized 46 strains of L. fermentum from various Kimere samples, collected from 11 different homesteats in the Mbeere community of Kenya 13 using different molecular biology methods 14. Briefly; Lactobacillus isolates were characterized and identified using biochemical methods such as carbohydrate fermentation patterns, API 50 CHL, growth temperatures, acid and bile salt tolerance, Gram and catalase reaction, and molecular methods such as species‐specific polymerase chain reaction (PCR), amplified rDNA restriction analysis (ARDRA), and partial sequencing of the 16S rDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea is for LAB capable of producing B vitamins to be used to fortify cereal based foods (Turpin et al, 2011). A study by Njeru et al (2010) showed that L. fermentum was also the dominant species isolated in kimere, a spontaneously fermented pearl millet dough produced in Kenya. All the L. fermentum strains were able to grow in vitro in medium containing 0.3% oxgall and 12 strains even grew in the presence of 3% oxgall.…”
Section: Productmentioning
confidence: 99%
“…Among the lactobacilli, L. plantarum and L. fermentum strains are particularly predominant in many traditional African fermentations (Mbugua, 1985;Olsen et al, 1995;Hounhouigan et al, 1993;Kostinek et al, 2005;Abriouel et al, 2006;Vizoso Pinto et al, 2006;Padonou et al, 2009;Njeru et al, 2010;Yousif et al, 2010;Oguntoyinbo and Narbad, 2012;Owusu-Kwarteng et al, 2012). The well-documented L. plantarum strain 299 V (Probi AB, Lund, Sweden) has been sold in some African countries for a few years, albeit in expensive capsule form, while less documented L. fermentum VRI003 (PCC) (Probiomics, Eveleigh, Australia) is also commercially available (Bhadoria and Mahapatra, 2011).…”
Section: Choice Of Multifunctional Strains For African Probioticsmentioning
confidence: 99%